2009
DOI: 10.1628/093245609789919685
|View full text |Cite
|
Sign up to set email alerts
|

Privatization and Universal Service Obligations

Abstract: Telecommunications, airlines, and postal services have similar economic features. However, they have followed different privatization patterns. While privatization of the universal service provider (USP) is common in telecommunications and airlines, it is by far less frequent in the postal sector. This paper analyzes how the size of the universal service obligation (USO) and the mechanisms traditionally used to finance it have prevented privatization in the postal sector. By using a model of a mixed duopoly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…numbers of employees contribute to high labor cost and inefficiency. High numbers of employees are claimed as the reason for the government not easily privatizing the company [9]. The case of PT Pos Indonesia reveals that high numbers of employees are due to the geographical situation of Indonesia.…”
Section: Highmentioning
confidence: 99%
See 2 more Smart Citations
“…numbers of employees contribute to high labor cost and inefficiency. High numbers of employees are claimed as the reason for the government not easily privatizing the company [9]. The case of PT Pos Indonesia reveals that high numbers of employees are due to the geographical situation of Indonesia.…”
Section: Highmentioning
confidence: 99%
“…In practice, numbers of success stories regarding privatization does not seem to apply with postal services. Postal industry is less likely to be successfully privatized [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the contemporary analyses written in the 1960s are valuable, but the authors of these studies lacked the theories, concepts and tools supplied by recent literature. Theoretical developments have provided valuable hypotheses on the motivations of politicians choosing between public ownership and privatisation (Shleifer and Vishny 1994;Boycko et al 1996;Bel and Calzada 2009), and have identified different objectives linked to privatisation policies Yarrow 1988, 1991). On the one hand, both the theoretical and the empirical literature have provided interesting results regarding the use of privatisation to obtain political support (Perotti 1995;Biais and Perotti 2002;Bortolotti et al 2003;Bel and Fageda 2009).…”
Section: Analysis Of the Objectives Of Privatisation In Puerto Ricomentioning
confidence: 99%